Land-grant Universities for the Future - Alexander H. Jones (The University of Alabama, 2022)
Review of the book: S.M. Gavazzi and E.G. Gee, Land-grant Universities for the Future: Higher Education for the Public Good. Baltimore, MD: Johns Hopkins University Press, 2018, 216 pages. ISBN: 9781421426853, hardback